Agriculture and Child Nutrition: An Analysis of Child & District- level Performance in Nepal. - Tapa, Ganesh; Shively, Gerald. (Tufts University. Tisch Library., 2016)
This presentation covers an analysis of child nutritional status through the lens of various factors, including economic status, caste status, maternal education, and geographic location.; Keywords: Scientific Symposium, Purdue University.; Nutrition School: NIL Symposium Presentations, 2013.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy